Due Diligence and Overlooked Evidence in the South China Sea Arbitration: A Note. (3rd July 2019) - Guo, Jianping; Wang, Peng
Abstract: In the South China Sea Arbitration, the Tribunal decided that China had not breached the due diligence obligation to protect and preserve the marine environment under Articles 192 and 194(5) of the United Nations Convention on the Law of the Sea concerning Chinese fishers fishing with explosives, but that China had breached the same obligation regarding Chinese fishers harvesting endangered species. This article looks at how the Tribunal interpreted and applied the due diligence obligation and argues, from a Chinese perspective, that there were facts overlooked by the Tribunal that China could have presented to counter the evidence of the Philippines, which might have been enough to affect the decision on destructive fishing had China participated in the Arbitration.